0
$\begingroup$

I'd like to find the solution of this PDE :

$$\frac{\partial f}{\partial t} = \frac{\partial f}{\partial x}+D\frac{\partial^2 f}{\partial x^2} $$

with $D$ a constant such that at infinity $t\rightarrow +\infty$ the solution is the solution of the equation is the solution of the ODE : $$\frac{\partial f}{\partial x}+D\frac{\partial^2 f}{\partial x^2}=0 $$

whose solution looks like this when you calculate it (it's an analytical formula) :

enter image description here

I'm wondering if I could find an analytical solution to my equation. $f(x,t)=F(x)+G(t)$ is indeed an obivous solution. But I'm wondering if to some extent one could impose some initial conditions : $f(x,t=0)=f_0(x)$.

EDIT: I found that what I'm looking for is the solution of the so called Mason-Weaver equation. It can be found here

$\endgroup$
2
  • 1
    $\begingroup$ I did not try to do the computations, but did you try to write the solution in the form $f(x,t)=a(x)b(t)$ and derive a possible expression for $a$ and $b$ in such a way that $f$ solves the PDE? Sometimes this variable splitting is a good approach...otherwise you can test even $f(x,t)=a(x)+b(t)$ $\endgroup$
    – Dadeslam
    Apr 29, 2020 at 9:11
  • 2
    $\begingroup$ The second equation is for $t \rightarrow \infty $ ? $\endgroup$
    – EDX
    Apr 29, 2020 at 9:15

2 Answers 2

2
$\begingroup$

Observe we have that \begin{align} \partial_t f = L f, \ \ f(0, x) = f_0(x) \end{align} then it follows \begin{align} f(t,x) = e^{tL}f_0. \end{align} Here, we see that \begin{align} L= \frac{\partial}{\partial x}+ D\frac{\partial^2}{\partial x^2}=: L_1+L_2. \end{align} Note that $[L_1, L_2] =0$, i.e. they commute. Then it follows \begin{align} e^{tL}f_0 = e^{tL_1}e^{tL_2}f_0. \end{align} Note that $g:=e^{tL_2}f_0$ solves the heat equation \begin{align} \frac{\partial g}{\partial t} = D\frac{\partial^2 g}{\partial x^2} \end{align} with initial condition $g(0, x) = f_0(x)$. Hence you can write out explicitly $g(t,x)$. Finally, we see that \begin{align} f(t,x) =e^{tL_1} g(x, t) = g(x+t, t) \end{align} since $e^{tL_1}g(x) = g(x+t)$.

$\endgroup$
1
$\begingroup$

First we wil suppose we can separate :

$$ f(x,t)=g(x)h(t)$$

The first equation becomes :

$$ \dfrac{dh}{dt}g=h(\dfrac{dg}{dx}+D\dfrac{d^2g}{dx^2}) \ (1)$$

So at the infinity the equation becomes:

$$ h(\infty)(\dfrac{dg}{dx}+D\dfrac{d^2g}{dx^2})= 0 \ (2)\\\ \\\dfrac{dh}{dt}_{t=\infty}=0 \ (3) $$

Solving for $g$ assuming $h(\infty)$ isn't null (depend on your physical modeling for coherence).

$$ \exists (A,B) \in \mathbb{R}^2, \ g:x\rightarrow A+Be^{-\frac{x}{D}}$$

Then from $(1)$ :

$$ \dfrac{dh}{dt}g=0 $$

We have $h$ constant (coherent with $(3)$) or $g$ null (evinced otherwise the problem has no utility !).

$$ f : (x,t) \rightarrow A'+B'e^{-\frac{x}{D}} $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.